2023
DOI: 10.3390/ma16020587
|View full text |Cite
|
Sign up to set email alerts
|

Superfunctional Materials by Ultra-Severe Plastic Deformation

Abstract: Superfunctional materials are defined as materials with specific properties being superior to the functions of engineering materials. Numerous studies introduced severe plastic deformation (SPD) as an effective process to improve the functional and mechanical properties of various metallic and non-metallic materials. Moreover, the concept of ultra-SPD—introducing shear strains over 1000 to reduce the thickness of sheared phases to levels comparable to atomic distances—was recently utilized to synthesize novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 122 publications
(224 reference statements)
0
15
0
Order By: Relevance
“…During solidification and equilibrium, a tetragonal DO 23 Al-3at.%Zr phase is formed with a wide range of cooling rates [13]. Interestingly, SPDs with huge strain or ultrasevere plastic deformation [14] made it possible to overcome these physical limitations and form unusual metastable super-saturated solid solutions, even in immiscible systems [15]. Application of huge shear straining to an Al-5at.%Zr alloy demonstrated that up to 1 at.% of Zr can be dissolved in an Al matrix at room temperature [16].…”
Section: Introductionmentioning
confidence: 99%
“…During solidification and equilibrium, a tetragonal DO 23 Al-3at.%Zr phase is formed with a wide range of cooling rates [13]. Interestingly, SPDs with huge strain or ultrasevere plastic deformation [14] made it possible to overcome these physical limitations and form unusual metastable super-saturated solid solutions, even in immiscible systems [15]. Application of huge shear straining to an Al-5at.%Zr alloy demonstrated that up to 1 at.% of Zr can be dissolved in an Al matrix at room temperature [16].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting observation that deserves mentioning is that after a certain threshold in strain perfect plasticity may break down leaving the stage to renewed strain hardening of the deforming material. 16,17) Again, it is not quite clear whether this resumption of strain hardening after a period of perfect plasticity without a change of the deformation path is universal or not.…”
Section: Perfect Plasticitymentioning
confidence: 99%
“…In addition, HPT clearly has the potential to become part of manufacturing processes. 17,126129) However, despite burgeoning research activity in nanostructured and ultrafine-grained materials produced by SPD, it is fair to say that so far, the practical outcomes of research have not met the expectations of industry. The prevailing sentiment is that without upscaling of the SPD processes, commercialisation of laboratory-proven technologies would not be accepted by industry and enjoy commercialisation successes.…”
Section: Hpt: Possible Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14) Such materials are sometimes referred to as superfunctional materials due to their superior properties. 15,16) For the most recent progress in the field of SPD, the readers are referred to a 2023 special issue of Materials Transactions, 17) which covered various aspects like processing methods, [18][19][20][21][22][23][24][25][26] structural/microstructural features, [27][28][29][30][31][32][33] mechanical/functional properties, nanostructured metallic and non-metallic materials [56][57][58][59][60][61][62][63][64][65][66][67][68] and heterostructured materials. [69][70][71][72] Among various SPD methods, ECAP and ARB have the potential for commercialization.…”
Section: Introductionmentioning
confidence: 99%